Resin composition for bonded magnet and bonded magnet using the same

JP2025021480AInactive Publication Date: 2025-02-14TODA KOGYO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021207351
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-21
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0020】 本発明のボンド磁石用樹脂組成物は、これを用いて成形した成形品は、Br(残留磁束密度)等の磁気特性を低下させることなく、耐熱性、曲げ強度·IZOD衝撃強度等の物性特性に優れ、しかも、耐冷熱衝撃性が高く、過酷な環境下でも使用出来るので、ボンド磁石用として好適である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021480000001
    Figure 2025021480000001
  • Figure 2025021480000002
    Figure 2025021480000002
  • Figure 2025021480000003
    Figure 2025021480000003
Patent Text Reader

Abstract

To provide a resin composition for bonded magnets, which exhibits excellent physical properties such as heat resistance, thermal shock resistance, bending strength and IZOD impact strength without being deteriorated in magnetic properties.SOLUTION: A resin composition for bonded magnets comprises at least magnetic powder, a PPS resin and a thermoplastic vinylidene fluoride-based resin, in which Mooney viscosity of the thermoplastic vinylidene fluoride-based resin at 121°C is 50 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for bonded magnets that has excellent physical properties such as heat resistance, resistance to cold and hot shocks, bending strength, and IZOD impact strength without compromising magnetic properties, and to a bonded magnet that uses said resin composition. [Background technology]

[0002] As is well known, bonded magnets have advantages over sintered magnets, such as being lighter in weight, having better dimensional accuracy, and being easily mass-produced even in complex shapes, and therefore are widely used in a variety of applications, including toys, office equipment, audio equipment, and motors.

[0003] Known magnetic powders used in bonded magnets include rare earth magnet powders, such as Nd-Fe-B, and ferrite particle powders. Rare earth magnet powders have high magnetic properties, but are expensive and have limited applications. On the other hand, ferrite particle powders have inferior magnetic properties compared to rare earth magnet powders, but are inexpensive and chemically stable, making them suitable for a wide range of applications.

[0004] Bonded magnets are generally made by mixing a rubber or plastic material with a magnetic powder and then molding the mixture in a magnetic field or by mechanical means.

[0005] In recent years, as various materials and equipment have become more productive and more reliable during use, there is a demand for higher performance of the bonded magnets used, including improved productivity, mechanical strength, and magnetic properties.

[0006] For example, bonded magnets are used in rotors and sensors in vehicles, etc., and there is a strong demand for high heat resistance and mechanical strength to extend the life of the equipment and for use at high speed rotation. For this reason, bonded magnets are used that use PPS resin as a binder resin, which is said to have high heat resistance and little deterioration of mechanical properties at high temperatures.

[0007] For example, Patent Document 1 proposes a compound for bonded magnets that has high heat resistance and excellent mechanical strength and magnetic properties by mixing PPS resin and PA resin in a specified ratio, while Patent Document 2 proposes a compound for bonded magnets that has high heat resistance and excellent mechanical strength and magnetic properties by adding modified polyolefins and glass fibers to PPS resin.

[0008] For example, Patent Document 3 proposes a resin composition for bonded magnets that contains a phosphorus-based antioxidant in order to obtain bonded magnets that experience little loss in strength even when exposed to high-temperature environments.

[0009] Furthermore, Patent Document 4 proposes a compound for bonded magnets that has excellent fluidity, high magnetic force, and excellent heat resistance without compromising mechanical strength, by mixing PPS resin and vinylidene fluoride rubber in a specified ratio. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2013-77802 A [Patent Document 2] Japanese Patent Application Publication No. 4-44304 [Patent Document 3] JP 2015-76572 A [Patent Document 4] Japanese Patent Application Publication No. 9-219312 Summary of the Invention [Problem to be solved by the invention]

[0011] However, bonded magnets using PPS resin have low toughness and there are concerns that they may crack immediately after injection molding or in hot and cold environments (heat shock), so there is a strong demand for high impact resistance and resistance to cold and hot shocks.

[0012] Therefore, the technical object of the present invention is to obtain a resin composition for bonded magnets that has excellent physical properties such as heat resistance, resistance to cold and hot shocks, bending strength, IZOD impact strength, etc., without deteriorating the magnetic properties. [Means for solving the problem]

[0013] The above technical object can be achieved by the present invention as follows.

[0014] That is, the present invention is a resin composition for bonded magnets consisting of at least a magnetic powder, a PPS resin, and a thermoplastic vinylidene fluoride resin, characterized in that the thermoplastic vinylidene fluoride resin has a Mooney viscosity of 50 or more at 121°C (Invention 1).

[0015] The present invention also relates to a resin composition for bonded magnets according to Invention 1, characterized in that the thermoplastic vinylidene fluoride resin has a tensile elongation of 400% or more (Invention 2).

[0016] The present invention also relates to a resin composition for bonded magnets according to either Invention 1 or Invention 2, characterized in that the content of the thermoplastic vinylidene fluoride resin relative to the PPS resin is 1.0 to 16.0% by weight (Invention 3).

[0017] The present invention also relates to a resin composition for bonded magnets according to any one of Inventions 1 to 3, characterized in that the content of the PPS resin is 5 to 30% by weight (Invention 4).

[0018] The present invention also relates to a resin composition for bonded magnets according to any one of Inventions 1 to 4, characterized in that the content of the thermoplastic vinylidene fluoride resin is 0.1 to 2.5% by weight (Invention 5).

[0019] The present invention also provides a bonded magnet molded using the resin composition for bonded magnets according to any one of Inventions 1 to 6 (Invention 6). Effect of the Invention

[0020] The resin composition for bonded magnets of the present invention is suitable for use in bonded magnets because molded articles made from it have excellent physical properties such as heat resistance, bending strength, IZOD impact strength, etc., without reducing magnetic properties such as Br (residual magnetic flux density), and also have high resistance to cold and heat shocks, allowing them to be used in harsh environments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described in detail below.

[0022] The resin composition for bonded magnets according to the present invention contains at least a magnetic powder, a PPS resin, and a thermoplastic vinylidene fluoride resin.

[0023] The magnetic powder in the present invention is not particularly limited, and magnetic powders typically used in bonded magnets, such as ferrite particles, rare earth magnetic powder, and soft ferrite particles, can be used.

[0024] The ferrite particles are preferably magnetoplumbite ferrite particles, and the magnetoplumbite ferrite particles are barium ferrite particles, strontium ferrite particles, barium-strontium ferrite particles, or these ferrite particles containing 0.1 to 7.0 mol % of one or more elements selected from Ti, Mn, Al, La, Zn, Bi, and Co, expressed by the formula AO·nFe2O3 (wherein A is Ba, Sr, or Ba-Sr, and n = 5.0 to 6.5).

[0025] The average particle size of the ferrite particles is preferably 1.0 to 5.0 μm, more preferably 1.0 to 2.0 μm, and the BET specific surface area is 1 to 10 m 2 / g is preferable, and 1 to 5m 2 / g, the coercive force iHc is preferably 119 to 557 kA / m (1500 to 7000 Oe), more preferably 119 to 398 kA / m (1500 to 5000 Oe), and the residual magnetization is preferably 100 to 300 mT (1000 to 3000 G), more preferably 100 to 200 mT (1000 to 2000 G).

[0026] Rare earth magnetic powder is an intermetallic compound that contains at least one rare earth element and at least one transition metal. Examples of rare earth magnetic powder include rare earth cobalt, rare earth-iron-boron, and rare earth-iron-nitrogen magnetic powders. In particular, when rare earth-iron-boron magnetic powder or rare earth-iron-nitrogen magnetic powder is used, a bonded magnet with excellent magnetic properties can be obtained.

[0027] The average particle size of the rare earth magnetic powder is preferably 1 to 120 μm, more preferably 1 to 80 μm, and the BET specific surface area is preferably 0.5 to 5 m. 2 / g is preferable, and 0.5 to 3m 2 / g, the coercive force iHc is preferably 239 to 1591 kA / m (3.0 to 20 kOe), more preferably 318 to 1114 kA / m (4.0 to 15 kOe), and the residual magnetization is preferably 0.3 to 1.8 mT (3.0 to 18 kG), more preferably 0.5 to 1.3 mT (5.0 to 13 kG).

[0028] The Nd-Fe-B magnetic powder may be used as is for kneading. However, if the Nd-Fe-B magnetic powder is a flaky powder, it is preferable to pulverize it with a jet mill, atomizer, ball mill, etc. to obtain higher fluidity and magnetic properties, and to reduce the average particle size to 100 μm or less.

[0029] Examples of the soft ferrite particle powder include Mn-Zn ferrite, Ni-Zn ferrite, Ni-Zn-Cu ferrite, Mn-Mg ferrite, carbonyl iron powder, sendust, etc. In addition, it is also possible to use soft ferrite whose composition is changed according to the frequency of the electromagnetic wave to be used.

[0030] The average particle size of the soft ferrite powder is preferably 1 to 150 μm, and more preferably 1 to 50 μm.

[0031] It is desirable to subject these magnetic powders to various surface treatments in order to prevent deterioration of magnetic properties due to oxidation, to improve compatibility with resins, and to increase the strength of molded products.

[0032] Examples of materials that can be surface-treated include silane-based coupling agents, titanium-based coupling agents, aluminum-based coupling agents, siloxane polymers, organic phosphoric acid-based surface treatment agents, inorganic phosphoric acid-based surface treatment agents, etc. In particular, by treating the surface of the magnetic powder in advance with a silane-based coupling agent, the strength of the molded product can be further improved.

[0033] The thermoplastic vinylidene fluoride resin in the present invention includes thermoplastic elastomers such as vinylidene fluoride-propylene hexafluoride copolymer resin, vinylidene fluoride-propylene hexafluoride-ethylene tetrafluoride copolymer resin, vinylidene fluoride-propylene pentafluoride copolymer resin, vinylidene fluoride-propylene-ethylene tetrafluoride copolymer resin, vinylidene fluoride-ethylene trifluoride chloride copolymer resin, vinylidene fluoride-perfluoroalkyl vinyl ether-ethylene tetrafluoride copolymer resin, etc. The thermoplastic vinylidene fluoride resins may be used alone or in combination of two or more kinds.

[0034] Thermoplastic vinylidene fluoride resins can be easily dispersed uniformly when mixed with PPS resin, and they have good moldability, making it possible to obtain molded products with excellent physical properties.

[0035] The thermoplastic vinylidene fluoride resin used in the present invention is a thermoplastic vinylidene fluoride resin having a Mooney viscosity at 121° C. of 50 or more.

[0036] Mooney viscosity is an index that indicates the ease of deformation of rubber, and the higher the value, the more difficult it is to deform and the higher the viscosity. The thermoplastic vinylidene fluoride resin in the present invention is a substance with rubber elasticity, and a Mooney viscosity of 50 or more at 121°C means that the resin has a higher viscosity or is harder than the specified value. Therefore, this includes cases where the resin does not show flow in the measurement of the Mooney viscosity at 121°C and therefore does not have a Mooney viscosity value.

[0037] By using a thermoplastic vinylidene fluoride resin having a Mooney viscosity of 50 or more at 121°C, a molded article having excellent heat resistance and mechanical strength, particularly excellent resistance to thermal shock, can be obtained. If the Mooney viscosity of the thermoplastic vinylidene fluoride resin is less than 50, the mechanical strength and resistance to thermal shock of the molded article will decrease, which is not preferable. The Mooney viscosity of the thermoplastic vinylidene fluoride resin at 121°C is preferably 55 or more, more preferably 60 or more.

[0038] The tensile elongation of the thermoplastic vinylidene fluoride resin is preferably 400% or more. If the tensile elongation is less than 400%, the mechanical strength and heat resistance of the molded product will decrease, which is undesirable. The tensile elongation of the thermoplastic vinylidene fluoride resin is more preferably 500% or more.

[0039] The PPS resin used in the present invention is not particularly limited, but the average molecular weight is preferably 10,0000 to 100,000. When a low molecular weight PPS resin is used, the melt viscosity is low, so the moldability of the injection molding composition is excellent, but the physical properties such as strength are poor. Conversely, when a high molecular weight PPS resin is used, the physical properties are excellent, but the viscosity is high, so that increasing the filling amount of the magnetic powder results in poor moldability.

[0040] Furthermore, the melt viscosity of the PPS resin can be selected appropriately depending on the magnetic powder, but is preferably within the range of 5 to 200 Pa·s at 310° C. If the melt viscosity is less than 5 to 200 Pa·s, the mechanical strength of the resulting resin composition for bonded magnets may decrease, while if the melt viscosity exceeds 200 Pa·s, the fluidity of the resin composition for bonded magnets may decrease significantly, making injection molding difficult.

[0041] There are no particular limitations on the molecular structure of PPS resin, including cross-linked and straight-chain types. If necessary, PPS resin may be blended with various elastomers such as rubber or elastic resins.

[0042] In the resin composition for bonded magnets according to the present invention, the thermoplastic vinylidene fluoride resin is preferably 1.0 to 16.0% by weight relative to the PPS resin. If the content of the thermoplastic vinylidene fluoride resin relative to the PPS resin is less than 1.0% by weight, the effect of improving physical properties such as heat resistance, cold and thermal shock resistance, bending strength, IZOD impact strength, etc. is reduced. If the content of the thermoplastic vinylidene fluoride resin relative to the PPS resin exceeds 16.0%, this is not preferable because the fluidity decreases. The content of the thermoplastic vinylidene fluoride resin relative to the PPS resin is more preferably 1.0 to 13.0% by weight, and even more preferably 2.0 to 9.0% by weight.

[0043] The resin composition for bonded magnets according to the present invention preferably contains 0.1 to 2.5% by weight of thermoplastic vinylidene fluoride resin. If the content of the thermoplastic vinylidene fluoride resin is less than 0.1% by weight, the effect of improving physical properties such as heat resistance, cold and thermal shock resistance, bending strength, IZOD impact strength, etc. is reduced. If the content of the thermoplastic vinylidene fluoride resin exceeds 2.5%, the flowability is reduced due to the increase in the thermoplastic vinylidene fluoride resin, which is not preferable. The content of the thermoplastic vinylidene fluoride resin is more preferably 0.2 to 2.0% by weight, and even more preferably 0.3 to 1.6% by weight.

[0044] The resin composition for bonded magnets according to the present invention preferably contains 5 to 30% by weight of PPS resin. If the content of PPS resin is less than 5% by weight, the resin composition for bonded magnets does not have sufficient fluidity, making it difficult to obtain a good molded product. If the content of PPS resin exceeds 30% by weight, the magnetic properties are degraded, which is not preferable. The content of PPS resin is more preferably 7 to 25% by weight, and even more preferably 10 to 20% by weight.

[0045] The content of magnetic powder in the resin composition for bonded magnets is preferably 69.6 to 94.5% by weight. If the content of magnetic powder is less than 69.6% by weight, the required magnetic properties cannot be obtained, which is not preferred. If the content of magnetic powder exceeds 94.5% by weight, the mechanical strength of the resulting bonded magnet decreases, and moldability such as flowability and recyclability decreases drastically, which is not preferred. The content of magnetic powder is more preferably 74.6 to 92.5% by weight, and even more preferably 79.6 to 89.5% by weight.

[0046] In the resin composition for bonded magnets according to the present invention, when the ferrite particles are used as the magnetic powder, the residual magnetic flux density Br is preferably 230 mT (2300 G) or more, more preferably 245 mT (2450 G) or more, as measured by the magnetic measurement method described below. The coercive force iHc is preferably 119 to 279 kA / m (1500 to 3500 Oe), more preferably 127 to 259 kA / m (1600 to 3250 Oe). The maximum energy product (BH)max is 10.3 kJ / m 3 (1.30 MGOe) or more is preferable, and 10.7 kJ / m is more preferable. 3 (1.35 MGOe) or higher.

[0047] In the resin composition for bonded magnets according to the present invention, when the rare earth magnetic powder is used as the magnetic powder, the residual magnetic flux density Br is preferably 300 mT (3000 G) or more, more preferably 350 mT (3500 G) or more, as measured by the magnetic measurement method described below. The coercive force iHc is preferably 636 to 955 kA / m (8000 to 12000 Oe), more preferably 676 to 915 kA / m (8500 to 11500 Oe). The maximum energy product (BH)max is 15.9 kJ / m 3 (2.00 MGOe) or more is preferable, and 19.9 kJ / m is more preferable. 3 (2.50 MGOe) or higher.

[0048] Next, a method for producing the resin composition for bonded magnets according to the present invention will be described.

[0049] The resin composition for bonded magnets according to the present invention can be obtained by a known manufacturing method for resin compositions for bonded magnets, for example, by uniformly mixing a magnetic powder, a PPS resin component and a thermoplastic vinylidene fluoride resin, melt-kneading the mixture using a kneading extruder or the like, and then pulverizing or cutting the kneaded mixture into granules or pellets.

[0050] The resin composition for bonded magnets according to the present invention may optionally contain lubricants for plastic molding and various stabilizers in order to improve moldability, improve heat resistance, prevent oxidative deterioration, and obtain anti-rust effects.

[0051] Examples of lubricants include carboxyl saturated / unsaturated fatty acids such as propionic acid, stearic acid, linoleic acid, oleic acid, malonic acid, glutaric acid, adipic acid, maleic acid, and fumaric acid, and compounds thereof such as metal soaps such as calcium stearate, magnesium stearate, and lithium stearate, fatty acid amides such as hydroxystearamide, ethylene bislauric acid amide, and ethylene bisoleic acid amide, waxes such as paraffin wax, polysiloxanes such as dimethylpolysiloxane and silicone oil, and fluorine compounds such as fluorine-containing oil.

[0052] As a stabilizer, it is preferable to add an antioxidant to prevent deterioration due to heat. Examples of the antioxidant include hindered amine stabilizers, hindered / less hindered phenols such as pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], metal deactivators such as N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionylhydrazine, phosphite, and thioether antioxidants, etc. In particular, the combined use of a hindered / less hindered phenol with a phosphite or metal deactivator is effective.

[0053] The antioxidant is preferably contained in the range of 0.1 to 1.0 wt %, more preferably 0.2 to 0.8 wt %, based on the total amount of the resin composition.

[0054] If necessary, a known release agent such as zinc stearate or calcium stearate may be added to the resin.

[0055] There is no particular restriction on the molding method for obtaining a molded product using the resin composition for bonded magnets of the present invention, and any of the known methods such as the transfer method, injection method, extrusion method, inflation method, calendar processing method, T-die method, blowing method, vacuum method, lamination method, spray-up method, foaming method, matched die method, SMC method, etc., can be used alone or in combination depending on the material properties of the resin composition for bonded magnets, the molding purpose, and the use, etc. In particular, for resin compositions for bonded magnets using thermoplastic resins, the injection method or extrusion method is preferred, as it is applicable to many industrial parts and allows continuous, high-speed, and mass production. EXAMPLES

[0056] Representative embodiments of the present invention will be described below, but the present invention is not limited to these.

[0057] The average particle size of the ferrite particles according to the present invention was measured using a "Sub-Sieve Sizer Model 95" (manufactured by Fisher Scientific).

[0058] The BET specific surface area of ​​the ferrite particles according to the present invention was measured using a fully automatic specific surface area meter Macsorb model-1201 (manufactured by Mountec Co., Ltd.).

[0059] The Mooney viscosity at 121° C. of the thermoplastic vinylidene fluoride resin was measured in accordance with ASTM-D1646.

[0060] The tensile elongation of the thermoplastic vinylidene fluoride resin was measured in accordance with ASTM-D638.

[0061] The molding density of the bonded magnet was determined by molding the resin composition for bonded magnets into a core in a mold with a diameter of 25 mm and a height of 10.5 mm using an injection molding machine, Model J55AD, manufactured by Japan Steel Works, Ltd., and then measuring the density with an "Electronic Specific Gravity Meter EW-120SG" (manufactured by Yasuda Seiki Seisakusho Co., Ltd.).

[0062] The melt mass flow rate (MFR) of the bonded magnet composition was determined in accordance with JIS K7210 by melting the composition at 330° C. and measuring the MFR under a load of 10 kg.

[0063] The magnetic properties of the bonded magnet (residual magnetic flux density Br, coercive force iHc, coercive force bHc, maximum energy product (BH)max) were determined by molding the resin composition for bonded magnets using an injection molding machine J55AD manufactured by Japan Steel Works, Ltd., in a mold with a diameter of 25 mm and a height of 10.5 mm while aligning the magnetic field at 318.3 kA / m (4 kOe), and then measuring the properties in a magnetic field of 1114.1 kA / m (14 kOe) using a "DC Magnetic Property Automatic Recorder 3257" (manufactured by Yokogawa Hokushin Electric Co., Ltd.).

[0064] The physical properties of the bonded magnets were measured using test piece molded body A with a total length of 80 mm, total width of 12.7 mm, and thickness of 3.2 mm, and cylindrical molded body B with an outer diameter of Φ30 mm, an inner diameter of 26 mm, and a height of 30 mm, both of which were obtained by injection molding the resin composition for bonded magnets using a J55AD injection molding machine manufactured by Japan Steel Works, Ltd.

[0065] The bending strength and IZDO impact strength of molded body A using the resin composition for bonded magnets were measured in accordance with the ASTM D790 and D256 standards using a computer-measured, precision universal testing machine, Model AG-1, manufactured by Shimadzu Corporation, and Model NO. 158, manufactured by Yasuda Seiki Seisakusho Co., Ltd.

[0066] A heat shock resistance test of molded body B using a resin composition for bonded magnets was performed using a thermal shock device TSA-73EL (manufactured by Espec Corporation) by performing 1,000 cycles of -20°C to 120°C (each temperature was held for 30 minutes) as one cycle, and the occurrence rate of cracks in molded body B was confirmed visually.

[0067] Example 1 Ferrite particles 83.43 parts by weight (average particle size 1.20 μm, BET value: 1.75 m 2 / g, coercive force 226kA / m (2850Oe), saturation magnetization 822Am 2 0.42 parts by weight of an aminoalkyl silane coupling agent was added to the ferrite particles (72 emu / g) and the mixture was heated and mixed at 120°C until uniform, yielding a surface-treated ferrite particle powder. 15.75 parts by weight of PPS resin (average molecular weight: 30,000, melt viscosity: 30 Pa s at 310°C) and 0.40 parts by weight of thermoplastic vinylidene fluoride resin-1 (melting point: 115°C, Mooney viscosity at 121°C: 72, tensile elongation: 700%) were added to the surface-treated ferrite particle powder and mixed thoroughly in a Henschel mixer to obtain a mixture of a resin composition for bonded magnets.

[0068] The obtained mixture of resin composition for bonded magnets was fed in a fixed amount to a twin-screw kneader and kneaded at a temperature at which the PPS resin melts. The kneaded product was taken out in the form of strands and cut into pellets measuring 2 mmΦ x 3 mm to obtain a resin composition for bonded magnets.

[0069] Table 2 shows the composition, molding density, MFR, and magnetic properties of the obtained resin composition for bonded magnets.

[0070] Table 3 shows the results of measuring the bending strength and IZOD impact strength of test piece molded body A obtained by injection molding of the resin composition for bonded magnets, and the yield rate of molded body B in the heat shock resistance test.

[0071] Examples 2 to 4 Except for varying the blending ratio of the ferrite magnetic powder, PPS resin, and thermoplastic vinylidene fluoride resin as shown in Table 1, resin compositions for bonded magnets were prepared in the same manner as in Example 1.

[0072] Examples 5 to 8 A resin composition for bonded magnets was prepared in the same manner as in Example 1, except that the thermoplastic vinylidene fluoride resin was changed to thermoplastic vinylidene fluoride resin-2 having a melting point of 165°C, a Mooney viscosity at 121°C: not flowing and therefore not measurable, and a tensile elongation of 500%, and the composition was changed in various ways as shown in Table 1.

[0073] Comparative Example 1 A resin composition for bonded magnets was prepared in the same manner as in Example 1, except that no thermoplastic vinylidene fluoride resin was used.

[0074] Comparative Examples 2 to 4 A resin composition for bonded magnets was prepared in the same manner as in Example 1, except that the thermoplastic vinylidene fluoride resin was changed to thermoplastic vinylidene fluoride resin-3 having a melting point of 115°C, a Mooney viscosity at 121°C of 35, and a tensile elongation of 200%, and the composition was changed in various ways as shown in Table 1.

[0075] [Table 1]

[0076] [Table 2]

[0077] [Table 3]

[0078] It was confirmed that the resin composition for bonded magnets according to the present invention has superior heat shock resistance properties compared to the resin composition for bonded magnets of Comparative Example 1, which does not contain a thermoplastic vinylidene fluoride resin. It was confirmed that the resin compositions for bonded magnets of Examples 3 and 4 and Examples 7 and 8, which contain a large amount of thermoplastic vinylidene fluoride resin, have slightly lower MFR values ​​and lower fluidity. In addition, the resin compositions for bonded magnets of Comparative Examples 2 to 4, which contain a thermoplastic vinylidene fluoride resin with a Mooney viscosity of 35 at 121°C, showed a decrease in the bending strength and IZOD impact strength of the molded body, and a decrease in the yield rate in the heat shock resistance test. [Industrial Applicability]

[0079] Therefore, by using the resin composition for bonded magnets of the present invention, it is possible to obtain molded articles that maintain high magnetic properties and physical properties while also having thermal shock resistance that allows them to be used in harsh environments, and that maintain their heat resistance and physical properties, making them suitable as materials for bonded magnets.

Claims

1. A resin composition for bonded magnets comprising at least a magnetic powder, a PPS resin, and a thermoplastic vinylidene fluoride resin, the thermoplastic vinylidene fluoride resin having a Mooney viscosity of 50 or more at 121°C.

2. 2. The resin composition for bonded magnets according to claim 1, wherein the thermoplastic vinylidene fluoride resin has a tensile elongation of 400% or more.

3. 3. The resin composition for bonded magnets according to claim 1, wherein the content of said thermoplastic vinylidene fluoride resin relative to the PPS resin is 1.0 to 16.0% by weight.

4. 4. The resin composition for bonded magnets according to claim 1, wherein the content of said PPS resin is 5 to 30% by weight.

5. 5. The resin composition for bonded magnets according to claim 1, wherein the content of said thermoplastic vinylidene fluoride resin is 0.1 to 2.5% by weight.

6. A bonded magnet molded using the resin composition for bonded magnets according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Plastic magnetic composition

    JP1992044304A

  • Composite for plastic magnet

    JP1997219312A

  • Compound for bond magnet and bond magnet

    JP2013077802A

  • Resin composition for bonded magnet, and bonded magnet using the same

    JP2015076572A